The main determinants affecting the spend in protected natural areas. The case of Cadí-Moixeró Natural Park, Catalonia, Spain - Jordi Seguí Urbaneja; Pablo Vidal-González; Saul Alcaraz; Víctor Dorado; Estela Inés Farías-Torbidoni (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and objectives. This study aimed to understand and analyse the main determinants affecting the (no) spend in protected natural areas. Method. Using a total of 1.119 on-site survey data from Cadí-Moixeró Natural Park, we analysed the visitor spending and identify influential sociodemographic, visit behavior, and motivational descriptors related to their likelihood of spending money during their visit. Natural Park is a man, in the early forties, with university studies who overnight in the park, which enables doing multiple group visits.